Dark Sides of Organizational Behavior and Leadership - Fors Brandebo, Maria; Alvinius, Aida (IntechOpen, 2019)
In recent years, scholars have focused more on the "dark sides of leadership." Both the negative and positive aspects of the relationship between leaders and followers are considered. But the relationship between leaders and followers is also influenced by the context in which the relationship occurs. Organizational aspects such as culture and structures are studied in relation to how negative leadership develops. Organizations, just like humans, are able to develop justifications for their actions, to self-aggrandize by claiming their exclusivity. In this book, the dark sides of organizational behaviors and leadership are considered from different aspects and contexts. The book contributes knowledge of how negative leadership develops, what part organizational structures play, and what the consequences are for the leader, the subordinates and the organization.